Real-Time Frequency Detection and Timer System for Shake Table Testing in Kontes Bangun Gedung Indonesia (KBGI) - I Raharja; Gde Dana; I Bhaskara; Ni Yuniari; I Kumara; I Darma (Penerbit Jurnal Indonesia, 2025)
This paper presents the design and implementation of a real-time frequency detection and timer system developed for the Kontes Bangun Gedung Indonesia (KBGI), a national building competition in Indonesia. The system integrates an MPU6050 accelerometer with an ESP32 microcontroller to measure the frequency of a shake table, transmitting the data via serial communication to a Node.js-based web application. The application processes the data and displays a real-time timer on a dashboard, enabling precise monitoring of shake table oscillations during the competition. Utilizing the zero-crossing method for frequency calculation, the system achieved reliable performance, successfully supporting KBGI by providing accurate frequency readings and timing control. This solution combines low-cost hardware with open-source software, offering an accessible and effective tool for structural testing in competitive settings. The system's success in the competition underscores its potential for broader applications in seismic simulation and educational environments.